Vision screening to detect refractive errors in three selected secondary schools in Birnin Kebbi, North West, Nigeria - Aliyu Hamza Balarabe; Ibrahim Adamu; Asmau Abubakar (Sahel Medical Journal, 2015)
Objective: The objective of this study was to determine the prevalence of uncorrected refractive error among students in three selected secondary schools in Birnin Kebbi metropolis as many children with poor vision due to refractive error remain undiagnosed and perform poorly in schools. Materials and Methods: This was a cross-sectional study that was conducted over a period of 2 months (May-June 2014). A total of 614 students were included from three randomly chosen secondary schools in Birnin Kebbi, Nigeria. Subjects were selected using random sampling technique from the list of students available through the help of their class teachers. Visual acuity (VA) was measured with a Snellen chart, while students with subnormal vision (VA ≤ 6/9) were examined using pinhole, and subsequently referred for detailed eye examination and retinoscopy evaluation. Results: The age range was from 11 to 20 years comprising 50.8% (n = 312) males and 48.2% (n = 302) females. Refractive error in either eye was present in 30 (4.8%) children. Of these, myopia was diagnosed in 18 (60%) children, and then hyperopia in 7 (23.3%), and astigmatism in 5 (16.7%) subjects. Spectacle coverage was low as only three pupils were found to be using glasses with lack of awareness and lack of access to eye care services as major barriers. Conclusions: Uncorrected refractive error is found among secondary schools students in Birnin Kebbi, and there is a need for the establishment of regular and effective school vision screening program to detect and refer patients for treatment.